Science and the Creative Spirit : Essays on Humanistic Aspects of Science. - Brown, Harcourt (Heritage., 1958)
Men on both sides of the science-humanities barrier feel an urgent need for mutual understanding. This symposium sponsored by the American Council of Learned Societies, stressed that it is only in a spirit of disinterested yet sincere evaluation that science and humanism can escape disastrous consequences in the future.